Gonioscopy-assisted Transluminal Trabeculotomy (GATT): Thermal Suture Modification With a Dye-stained Rounded Tip. Issue 6 (June 2016) - Grover, Davinder S.; Fellman, Ronald L.
Abstract : Purpose: To describe a novel technique for thermally marking the tip of a suture, in preparation for a gonioscopy-assisted transluminal trabeculotomy. Patient: One patient was used as an example for this technique. Methods: Technique report. Results and Conclusions: The authors introduce a modification of a novel surgical procedure (GATT) in which a suture is marked and thermally blunted allowing a proper visualization while performing an ab interno, minimally invasive, circumferential 360-degree suture trabeculotomy. The authors have previously reported on the GATT surgery with the use of an illuminated microcatheter, which allowed for visualization of the tip of the catheter as it circumnavigated Schlemm canal. This modification allows for similar visualization of the tip of the suture, however, is much more cost-effective while still maintaining similar safety. Abstract : Supplemental Digital Content is available in the text.